Estudio de factibilidad para la creación de un centro de distribución de frutas tropicales en el departamento de córdoba año 2018 (2019)
Feasibility study for the creation of a tropical fruit distribution center in the department of Córdoba Location: City of Lorica - Córdoba, Br / Campo Alegre, cll / 12b, Km 90, North zone Vía San antero. Business opportunity: Provide transportation and storage services of tropical fruits of the Córdoba department. Competitors: Currently in the department there are only competitors of informal transport and storage warehouses that do not provide the transport service, from the above we see the business opportunity in the creation of a distribution center that provides these services. Services: Transportation and storage from the start point to the end point. Average price of the transport service (250km-18.5t): $ 1,249,387 Average storage service price (3t for one week): $ 131,936 Project investment budget: The fixed investment is: $ 2,951,653,965 Profitability: The IRR of the Project is 33% Net Present Value (NPV): The net present value of the project is $ 2,311,695,288 R / BC = 2.17 Cost benefit ratio, for every 1 peso invested in the project, 2.17 pesos are generated